Internalisasi Makna Filosofi Tradisi Kirim Dawuhan sebagai Cara Meningkatkan Keterampilan Sosial pada Generasi Muda - Nadia Nur Aini; Poerwanti Hadi Pratiwi; Sudrajat (IAIN Madura, 2026)
The phenomenon of social skills today is one of the challenges in the field of education in the midst of the current development of the times. Minimal social skills for students can cause problems such as moral crises and bullying that lead to the loss of the nation's identity. Internalizing the values of local wisdom through school-based learning is one effort to improve students' social skills. This research aims to explore the philosophical meaning contained in the Kirim Dawuhan tradition as a way to improve students' social skills. The method used in the research is qualitative with a descriptive type. Data collection was carried out through observation, interviews with 10 informants, and documentation. This study uses data analysis techniques from Miles and Huberman through the stages of data condensation, data presentation, and conclusion drawn. The results of the study show that the Kirim Dawuhan tradition contains elements of social skills, including the values of mutual cooperation, tolerance, consensus deliberation, and social care. The internalization of local wisdom values in these traditions can be done through social studies learning based on local wisdom and cultural festivals in schools. Both activities can improve social skills, especially in the field of education, so that it is the right strategy in minimizing the negative impact of globalization and preserving the tradition of Kirim Dawuhan in Blitar Regency, so that it does not become extinct.